Implementasi Program Sekolah Ramah Anak di SD Negeri 30 Pangkalpinang Dan SD Negeri 37 Pangkalpinang - Kusnita Kusnita; Indah Kusuma Dewi; Ali Mashar (EDOIS: Journal of Islamic Education, 2023)
The increasing prevalence of many types of child violence serves as a convincing rationale for the necessity of protecting children's rights. To ensure the fulfillment of children's rights, it is imperative to establish an education system that can effectively generate a conducive learning environment. SD Negeri 30 Pangkalpinang and SD Negeri 37 Pangkalpinang are educational institutions that have adopted the Child Friendly School program in order to ensure that children have access to high-quality education and their rights are upheld. The objective of this study is to analyze the implementation mechanism and endeavor to meet the components of child-friendly schools in SD Negeri 30 Pangkalpinang and SD Negeri 37 Pangkalpinang with more scrutiny. This study employed a descriptive-qualitative methodology. Data collection employed approaches such as observation, interviews, and documenting. In addition, the acquired data was evaluated utilizing the Miles and Huberman analytical model, which encompasses data gathering processes, data reduction, data presentation, and conclusion derivation. The data validity test employed both source triangulation and technique triangulation methodologies. The present investigation yielded the subsequent findings: (1) The implementation process of the Child-Friendly School program in SD Negeri 30 Pangkalpinang and SD Negeri 37 Pangkalpinang consists of four stages: preparation through socialization, planning by creating an innovative program, implementation by executing the innovative program, and monitoring and evaluation by engaging the school's internal team. (2) SD Negeri 30 Pangkalpinang and SD Negeri 37 Pangkalpinang have successfully met all six indicators of child-friendly schools. However, in terms of educators and education personnel being trained in children's rights, teachers and staff in both schools still require ongoing training in this area.